Should humans interfere in the lives of elephants? - Lötter, H. P. P. (Koers, 2005)
Culling seems to be a cruel method of human interference in the lives of elephants. Culling is generally used to control population numbers of highly developed mammals to protect vegetation and habitat for other species. Many people are against human interference in the lives of elephants. In this article aspects of this highly controversial issue are explored. Three fascinating characteristics of this ethical dilemma are discussed in the introductory part, and then the major arguments raised against human interference in the lives of elephants are evaluated. These arguments are the following: First, that nature should be allowed to run its course and establish its own balance; nature will thus solve the problem of elephant over-population. The second argument raised by animal-rights activists as well as by animal-welfare groups either claim that animals have rights that humans must respect at all times, or that all sentient beings have interests that humans ought to respect, as those beings can experience pleasure or pain. The third argument often associates culling elephants as method for population control with the commercial use and exploitation of wilderness areas. Many people argue that it is unethical to use wildlife as a sustainable resource for fighting poverty. In conclusion it is stated that despite these arguments human